Islam dan Kepemimpinan Perempuan: Prototipe Leadership Ratu Balqis Perspektif Tafsir Al-Azhar - Setiawati, Poppy; Nur, Afrizal; Khairiah, Khairiah; Amin, Saidul (Al-Qudwah, 2024)
Women's leadership remains a subject of debate within the Islamic world, leading to various movements advocating for women's rights to be equal to men's. On the other hand, the perception that women prioritize emotions over logic has contributed to the notion that women are unsuitable for leadership roles. However, in reality, many women have proven themselves capable of leading institutions, organizations, and even nations. The Qur'an narrates a story of female leadership through the figure of Queen Balqis, who ruled the kingdom of Saba'. The purpose of this article is to explore the leadership prototype of Queen Balqis as depicted in Buya Hamka's Tafsir Al-Azhar. This research is a library-based study, with the primary data source being the Tafsir Al-Azhar, as well as secondary sources, including books and articles relevant to the research. The results of this study reveal that, from Hamka's perspective, Queen Balqis' leadership prototype embodies several key characteristics that are both relevant and valuable in the context of modern leadership. Analysis of Hamka's works, particularly Tafsir Al-Azhar, reveals that Queen Balqis possessed the following leadership qualities: first, wisdom and democracy. Hamka highlights how Queen Balqis demonstrated intelligence and wisdom in leading her people. Her decision to test the wisdom of Prophet Solomon by sending gifts reflects her ability to think democratically. Second, a diplomatic and peace-loving leader, Hamka, emphasizes that diplomacy is evident when a leader skillfully influences their followers to accept desired agreements and negotiations. Third, an intelligent and meticulous leader: Queen Balqis is portrayed as a smart, quick-thinking, cautious, and meticulous leader in making decisions. These three qualities in Queen Balqis make her a worthy role model for female leaders today.Abstrak: Kepemimpinan wanita masih menjadi suatu perdebatan dalam dunia Islam, akibatnya banyak timbul gerakan-gerakan yang menjunjung hak-hak wanita agar bisa disetarakan dengan laki-laki. Di sisi lain karakter wanita yang mengedepankan rasa dari pada logika membuat wanita seakan tidak layak menjadi pemimpin. Padahal kenyataannya banyak perempuan mampu menjadi pemimpin di suatu lembaga, organisasi bahkan negara. Di dalam Al-Qur’an terdapat kisah tentang kepemimpinan wanita yaitu kepemimpinan Ratu Balqis yang memimpin sebuah negeri bernama Saba’. Tujuan artikel ini untuk mengetahui prototipe leadership Ratu Balqis dalam Tafsir Al-Azhar karya Buya Hamka. Jenis penelitian ini merupakan penelitian pustaka, data primer dalam penelitian ini adalah kitab Tafsir Al-Azhar, sedangkan data sekunder adalah buku-buku dan artikel yang relevan dengan penelitian. Hasil penelitian ini menunjukkan bahwa prototipe kepemimpinan Ratu Balqis dalam perspektif Hamka mencerminkan beberapa karakteristik utama yang relevan dan berharga dalam konteks kepemimpinan modern. Analisis terhadap karya-karya Hamka, terutama tafsir Al-Azhar, mengungkapkan bahwa Ratu Balqis memiliki sifat-sifat kepemimpinan berikut: pertama, kebijaksanaan dan demokratis: Hamka menyoroti bagaimana Ratu Balqis menunjukkan kecerdasan dan kebijaksanaan dalam memimpin rakyatnya. Keputusan Balqis untuk menguji kebijaksanaan Nabi Sulaiman dengan mengirimkan hadiah menunjukkan kemampuannya untuk berpikir demokratis. Kedua, pemimpin yang diplomatis dan cinta damai, diplomasi seorang pemimpin dapat dilihat ketika ia pandai mempengaruhi orang-orang yang dipimpin supaya bisa menerima suatu kesepakatan dan perundingan yang diinginkan. Ketiga, pemimpin yang cerdas dan teliti, Ratu Balqis adalah pemimpin yang cerdas, berpikir cepat, bersikap hati-hati dan teliti dalam memutuskan suatu perkara. Tiga kriteria tersebut ada dalam diri Ratu Balqis yang layak dijadikan role model oleh para pemimpin perempuan saat ini.